(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Self-emulsifying drug delivery systems are a promising approach for the formulation of drug compounds with poor aqueous solubility. The main objective of this work was to formulate liquid and solid-self emulsifying drug delivery systems for poorly soluble aripiprazole. Aripiprazole is an atypical anti-psychotic drug used in the management of schizophrenia. The maximum solubility of aripiprazole was found in oleic acid (oil), Tween 80 (surfactant) and Transcutol P (co-surfactant). The L-SMEDDS were formulated in different ratios of oil: s-mix (surfactant: co-surfactant) from 1:9 to 9:1. For the formulation of stable SMEDDS, micro-emulsion region was identified by constructing pseudo-ternary phase diagram by phase titration method. The optimized F4 formulation was at the ratio of 4 (oil): 6 (s-mix). In-vitro drug release of F4 was significantly higher (99.89%) when compared to the pure drug (43.63%) in 1 hour. The F4 formulation had a droplet size of 115.9 nm and zeta potential of -24.9 mV. The pre-compression and post-compression parameters of the optimized S-SMEDDS formulation (SS1) containing Neusilin US2 as solid adsorbent were within the limits as per the official requirements of the Pharmacopoeia. SS1 formulation showed a better drug release (97% in 20 minutes) when compared to the marketed drug (59.75%) and pure drug (19.77%). In conclusion, this study illustrated that adsorption to solid carrier technique could be a useful method to prepare the solid SMEDDS tablets from liquid SMEDDS, which can enhance the solubility and improve the in-vitro drug release of aripiprazole.